Research on Meso-Damage Experiment and Simulation in the Anchorage Bonding Interface Between Rock Bolt and Rock Mass - Yaxin Liu; Minglu Xing; Tongbin Zhao; Fenghai Yu; Longfei Li; Shiwei Chen; Xiaohao Wang (Shock and Vibration)
Anchorage failure occurs mostly at the anchorage interface, and the mechanical mechanism of the anchorage interface is the key point and difficulty in the analysis and research of anchorage. In order to study the mechanics and failure mechanism of the anchorage interface, the shear failure characteristics of the anchorage interface and the deformation rule of the anchored rock under different rib spacings were analyzed through the indoor plane anchorage pull-out test. Reasonable rib spacing can significantly improve the shear strength of the anchored solid. Finite element software ABAQUS was used to create an axisymmetric plane model of rock bolt pull-out under different rib conditions to simulate the whole process of rock bolt pull-out and anchorage interface failure. The results show that during the pull-out process of anchorage rock mass, stress concentration zones occur at rib corners, and peak shear stress moves to the depths of the anchorage section. As the load increases, cracks emerge from the top of the rib and the edge of the rib angle of the rock bolt and propagate to the deep anchorage along the edge of the costal angle, resulting in damage at the rock mass interface. Load–displacement curves of different transverse rib shapes, heights, widths, and spacings indicate that rib changes affect the anchor-bearing limit. The anchoring failure mode changes from rib wear and spreading slip, rib shear convex body propagation to interfacial crack propagation, and rib causes varying degrees of damage to the surrounding rock mass. Therefore, reasonable rib parameter improvements can enhance anchoring force performance.